Comment les usages des marques de territoire et de la symbolique régionale bretonne peuvent-ils contribuer au développement de la langue bretonne et de la culture régionale ? - Roseline Le Squère (La Bretagne Linguistique, 2015)
This article follows up on a paper presented in 2013 and references a research project carried out from 1996 to 2018. Drawing on examples of situations of public, bilingual and symbolic marking in several areas of Brittany, it examines the links between culture and the economy. How do they function? When the regional language is used in the public space for no other reason than to allow an exchange between speakers of that language, is it still a language? And what future is secured for the language through these uses? The article examines these sociolinguistic fields by presenting language as an unending string of social practices, a continuum of situations and environments that are themselves social. Through these public display practices, which are necessarily social and in many cases economic, new relationships to the object language are established through a modification of the communication codes. What is important here is not so much the intention to address the public with words but rather what these words reference. Does this then make the language a paralinguistic element? Such situations can bring together economists, sociolinguists, and so on, to contribute to the debate in order to identify, together, how we can act to better control the balance between culture’s contribution to the economy and the economy’s contribution to culture.